The Influence of Reading Activities in the RADEC Model on Reading Comprehension Skills of Grade VI Elementary School Students on Natural Science Soil Materials - Fhilrizki, Salma Ihsani; Sopandi, Wahyu; Sujana, Atep (International Conference on Elementary Education, 2022)
In the implementation of the RADEC learning model, students still have not carried out the stages of reading to the fullest. This study aims to analyze the effect of reading activities on the RADEC model on reading comprehension skills. The research method used is descriptive quantitative with survey techniques and learning evaluation tests. The sample was determined intentionally for 26 sixth-grade students at SDN 093 Tunas Harapan Cijerah. The analysis technique carried out in this study is to determine the implementation of reading by using a survey questionnaire for the implementation of reading activities using the google form and to determine the average value of understanding the material on the pre-learning test and evaluation test. The results of the analysis show that the average students' understanding skills on the pre-learning and evaluation tests obtained by students include (1) students who read 75% of the material get an average score of 80 and 8; (2) students who read 50% of the material got an average score of 76.7 and 67.8; and (3) students who read 25% of the material got an average score of 62.5 and 42.5. The conclusion of this study is that reading activities in the RADEC model affect students' reading comprehension skills. The implementation of reading the material effectively and thoroughly will determine the understanding of the learning material. The results of this study are expected to be an evaluation material for implementing learning in schools to train children to carry out reading activities effectively.